Medication underuse in real-life practice: the impact of galcanezumab towards achieving very low frequency episodic migraine in a southeast Asian middle-income nation - Wanakorn Rattanawong; Prakit Anukoolwittaya; Akarin Hiransuthikul; Thanakit Pongpitakmetha; Auranee Trisataya; Sekh Thanprasertsuk; Alan Rapoport (The Journal of Headache and Pain)
Abstract Background Migraine progression, particularly from episodic to chronic migraine (CM), increases disease burden and healthcare costs. Understanding the new concept of “Medication Underuse Headache” should encourage the health care provider to consider early intervention with calcitonin gene-related peptide (CGRP) monoclonal antibodies. Galcanezumab given early in the course of the disease, may prevent migraine chronification and have a robust response, moreso than when initiated in later stages of migraine. We aimed to determine the efficacy of galcanezumab in achieving very low-frequency episodic migraine (VLFEM) among patients with high-frequency episodic migraine (HFEM) and CM in a real world-setting in Thailand. Methods A single-center, retrospective real-world, cohort study was conducted between 2023 and 2024. Adults aged 18 years or more who were diagnosed with HFEM or CM were included in this trial and categorized into two groups: galcanezumab and oral migraine preventive medication (OMPM). In the galcanezumab group, oral preventive medications were slowly tapered off within 3 months. The primary outcome was the differences in percentage of patients achieving VLFEM at months 3 and 6 between the two groups. Secondary outcomes included the differences in migraine class improvement, sustained response, and headache day reduction. Results A total of 62 patients (31 in each group) were included: median age was 36.5 (IQR: 29.0–48.0) and 82% were female. There were no significant differences in the baseline demographic features between the two groups. The cumulative incidence of patients achieving VLFEM was significantly higher among the galcanezumab group compared to OMPM group (45.2% vs. 19.4% at month 3 and 52.9% vs. 32.4% at month 6, p = 0.03). After 6 months of follow-up, patients with HFEM who received galcanezumab were significantly more likely to achieve any improvements in migraine class compared to those who received OMPM (92.9% vs. 46.7%, p = 0.01). Among 15 patients who achieved VLFEM at month 3, 81.8% (9/11) of those who received galcanezumab and 50.0% (2/4) of those who received OMPM were able to sustain VLFEM at month 6. Conclusions This study emphasizes the benefit of early anti-CGRP therapy initiation, especially in patients with fewer headache days, and highlights the need for accessible migraine-specific treatments in low- to middle-income countries.